Community policing in America - Wilson, Jeremy M. (Criminology and justice studies, 2006)
Introduction -- Defining community policing and researching its implementation -- Police organizations as open systems -- Organizational context and community policing -- Organizational structure and community policing -- Organizational context and organizational structure -- Models, data, and analysis -- Findings -- Conclusions and policy implications.